ANALISIS HIRARKI PUSAT PELAYANAN PERKOTAAN DI KOTA BITUNG - Lalu Renaldo Patrik; Wieske Ch. Rotinsulu; Sherly Gladys Jocom (AGRI-SOSIOEKONOMI, 2021)
The first objective of this study is to identify the availability and suitability of standardization of government, social, and economic facilities in the city of Bitung. The second is to analyze the Hierarchy of Service Centers in Bitung City. And the third is to analyze the suitability of the service center in the Bitung City RTRW 2013 – 2033 to the existing conditions. The type of data used in this research is secondary data. The data collection methods used are observation, literature review, and documentation study. Furthermore, the data were analyzed using the scalogram analysis method, centrality index, and gravity analysis. The first result of this research is based on the conformity of service standardization according to SNI 03-1733-2004, most of the service facilities in Bitung City have met the service standard. The second is based on the results of the scholagram analysis, order/hierarchy I, namely Madidir District. Based on the analysis of the marshal centrality index, Madidir and Maesa sub-districts occupy the first order/hierarchy. Based on gravity analysis, three sub-districts have been found to have weak regional interaction values with Madidir and Maesa sub-districts. And the third, based on the RTRW of Bitung City in 2013-2033, it has undergone changes in accordance with the dynamic development of the city.